Model Kepemimpinan Daud dan Implikasinya Bagi Kepemimpinan Masa Kini - Pelmelay, Ernavina; Pelmelay, Astrilily (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
David's leadership is a benchmark for leadership today. David was a strong influence in becoming King over the Israelites. David's leadership sets an example for today's leadership by being a leader who knows God's heart in order to lead with courage and direction from God. He can make decisions firmly because he has a life that knows God. The purpose of this study is so that today's leaders can reflect and apply David's leadership model in the Church and spiritual organizations they lead. Literature review of David's life and experts' views on leadership. The research method used is a literature study by collecting data from various documents, books, journals, other articles so as to get the results of David's leadership style that can be applied to today's leadership is a leader who knows the heart and will of God and is able to make decisions and is able to be responsible for the decisions taken.